Financial Performance Analysis of Sharia Business Unit Life Insurance Companies in Indonesia 2019-2023 - Fadhillah, Rizky; Nur Fajeriati, Ariana (Pusat Riset dan Inovasi Nasional, 2024)
Indonesia's economy developed better than the previous year and remained stable due to people's economic activity. With the development of the economy and community activities, there are more and more possibilities of risks that arise and threaten humans. From this, the insurance industry has also begun to become one of the supporting pillars in economic growth as one of the insurance solutions for goods, loans, and even their lives. So it requires every person who wants to do insurance to understand and know the performance of insurance companies as an option in investing to avoid losses. This study aims to conduct an in-depth analysis of the performance of life insurance companies of sharia business units through their finances during the 2019-2023 period. The method used is financial ratio analysis with the Early Warning System (EWS) method which includes solvency ratios, profitability, liquidity, premium stability, and technical liabilities. The data used comes from the company's publicly available annual financial statements. The results of the analysis show that life insurance companies of sharia business units in Indonesia generally show poor corporate performance in the research period. Some ratios show negative trend results, which can be detrimental to the people who invest.This research provides valuable insights for stakeholders in the Islamic life insurance industry in understanding the factors that affect the company's financial performance. The implications of these findings can be used as a foundation for strategic decision-making, product development, and increased oversight of risk management